Influence of cobalt on performance of Cu-CeO2 catalysts for preferential oxidation of CO - Malwadkar, Sachin; Bera, Parthasarathi; Satyanarayana, C. V. V. (Journal of Rare Earths, 2020)
{Copper and cobalt oxides supported on CeO2 were investigated for preferential oxidation of carbon monoxide (CO-PROX) in the presence of excess hydrogen and CO2. (CuO)(1-x)(Co3O4)(x/3)-(CeO2)(2.5) (x = 0, 0.25, 0.50, 0.75, 0.85 and 1) catalysts were prepared by coprecipitation method. These mixed oxide catalysts were characterized by several physicochemical techniques, such as BET surface area (SBET), X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), temperature programmed reduction (TPR) and X-ray photoelectron spectroscopy (XPS). XRD studies show the peaks related to CuO and Co3O4 phases in copper and cobalt containing CeO2 catalysts. The average particle size of the CeO2 crystallites is in the range of 8-10 nm as evaluated from HRTEM studies. XPS studies demonstrate that Cu, Co and Ce in (CuO)(1-x)(Co3O4)(x/3)-(CeO2)(2.5) catalysts are presented in +2 and +1, +3 and +2 and +4 and +3 oxidation states, respectively. The catalyst with x = 0.75 shows better activity and selectivity towards CO-PROX. Though the catalyst with only copper (CuO-CeO2
Keywords: CO-PROX; Cu-CeO2; H2O addition; Methanation; XPS; XRD